1, 5‐Diaza‐3, 7‐Diphosphacyclooctane Bis‐Ligand Nickel(II) Complexes as Oxygen Reduction Catalysts for Proton‐Exchange Membrane Fuel Cells. Issue 7 (14th May 2019) - Kadirov, Marsil; Karasik, Andrey; Nizameev, Irek; Spiridonova, Yulia; Khrizanforov, Mikhail; Kadirov, Danis; Nizameeva, Guliya; Khrizanforova, Vera; Mukhametzyanova, Dina; Budnikova, Yulia; Sinyashin, Oleg
Abstract : Membrane electrode assemblies (MEAs) with 1, 5‐diaza‐3, 7‐diphosphacyclootane organometallic bis ‐ligand nickel(II) complexes [Ni(P Ph 2 N Ph 2 )2 ] 2+ 2 . [BF4 ] − [1(Ph‐Ph)] and [Ni(P Ph 2 N Bn 2 )2 ] 2+ 2 . [BF4 ] − [2(Ph‐Bn)] as a part of oxygen reduction reaction (ORR) catalysts for proton‐exchange membrane fuel cells (PEMFCs) are built and tested. The complexes are characterized by atomic force microscopy (AFM), electron spin resonance (ESR), cyclic voltammetry (CV), and differential scanning calorimetry‐thermogravimetric analysis (DSC‐TGA). Electrochemical activity toward ORR and catalytic stability of compounds is tested by chronoamperometry (CA). The electrochemical activity of catalysts and ORR mechanisms is studied by rotating disk electrode (RDE). A performance analysis of the PEMFC is carried out. A peak power density of about 11.84 mW cm −2 and a current density of 80 mA cm −2 are measured for 2(Ph‐Bn)/C cathode and Pt/C anode catalysts, respectively. Chronoamperometric tests in 0.5 m  H2 SO4 for 3 h show an excellent stability for the compound 2(Ph‐Bn). The performance of 1(Ph‐Ph)/C catalyst and the chronoamperometric stability of 1(Ph‐Ph) are worse. A possible relationship between the catalysts' performance and basicity of pendant amines on the base of the proposed ORR mechanism with two metal centers is discussed. Abstract : Membrane electrode assemblies with 1, 5‐diaza‐3, 7‐diphosphacyclootane organometallic bis ‐ligand nickel(II) complexes as part of oxygen reduction reaction catalysts for proton‐exchange membrane fuel cells are built and tested. Microscopic, spectroscopic, and electrochemical characterization of the complexes is given. Performance and chronoamperometric stability of [Ni(P Ph 2 N Pn 2 )2 ] 2+ /C catalysts are worse than that of [Ni(P Ph 2 N Bn 2 )2 ] 2+ /C. A possible relationship between the catalysts' performance and basicity of pendant amines is discussed.